Validación del sistema de purificación de agua, para una planta nacional de fabricación de productos oftálmicos - Saavedra Gamboa, Mirian Evelyn (2013)
This thesis work presents the validation study of a system of water purification, for a national manufacturing plant of ophthalmic products, with the aim of establishing documented evidence that the mentioned system complies consistently with established quality specifications. To achive this purpose, was developed and executed a validation Protocol, also developed a sampling plan involving all the water system fir the realization of the first validation phase, which was conducted an exhaustive monitoring for the period of one month.. Physicochemical and microbiological analyses were performed to samples from each sampling point. Also contains the evaluation of results obtained in the analysis: appearance, pH, conductivity, total solids, oxidizable substances, heavy metals and microbiological count; for which took into account the specifications set forth by the American Pharmacopoeia and the Ministry of health, for drinking water and purified water, respectively. Still these specifications our acceptance criteria that allows us to determine the quality of the purified water obtained and the behavior of the water purification system, using for this purpose the control graphs. According to the results obtained are shows that the water purification system is under control and that its product, purified water, in compliance with stated specifications